Pengaruh Kualitas Informasi dan Kualitas Layanan Terhadap Kepuasan Konsumen: Studi pada Pengguna Aplikasi Haji Pintar - Nanda Rizki Maulidia; Laily Muzdalifah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to determine the influence of information quality and service quality on consumer satisfaction among Smart Hajj application users. Based on the Accidental Sampling method, a sample of 75 respondents was obtained. The analysis method uses multiple linear regression. From the results of the t test, it shows that the information quality variable has a calculated t value of 10.341 > t table 1.995 and a significance value of 0.000 < 0.05, so H1 is accepted, which means that the information quality variable has a significant effect on the dependent variable consumer satisfaction, the service quality variable has a calculated t value. amounting to 3.047 > t table 1.995 and a significance value of 0.003 < 0.05, then H2 is accepted, which means that the independent variable service quality has a significant effect on the dependent variable consumer satisfaction. From the results of the F test of 90.907 > F table 3.12, H3 is accepted, which means that there is a positive influence simultaneously (simultaneously) between the independent variable and the dependent variable. Then based on the results of the determination test or R2 test it is 0.716, this means that 71.6% of the consumer satisfaction variable can be explained by the information quality and service quality variables.